ANALISIS KEPUASAN MAHASISWA TERHADAP LAYANAN APLIKASI SIKAMU MENGGUNAKAN MOBILE SERVICE QUALITY - Lety Lestari; RG Guntur Alam; Monsya Juansen; Sri Handayani (PT. Hasba Edukasi Mandiri, 2025)
The Advancement of digital technology has encouraged higher education institutions to provide mobile-based academic services to enhance efficiency and convenience of students. Universitas Muhammadiyah Bengkulu developed the SIKAMU application as a platform to access academic information online. This study aims to analyze student satisfaction with the SIKAMU application using the mobile service quality (M-SERVQUAL) approach, which includes five dimensions: Efiiciency, reliability, security, interface design, and feature conformity. The research method used is descriptive quantitative, with data collected through questionnaires distributed to 129 active student from the faculty of engineering. The analysis result show that students are generally very satisfied with the SIKAMU services, with an average Customer Satisfaction Index (CSI) of 97% the feature conformity dimension received the highest satisfaction score (100%), while efficiency received the lowest (94%), though still with in the “very satisfied” category. The gap analysis between expectations, expectations, except for efficiency, which still requires improvement. This study concludes that the SIKAMU application has successfully met students academic service needs digitally; however, improvements in efficiency and security are recommended to maintain and enhance service quality.